Personal Selling Memoderasi Nilai yang Dirasakan dan Harga terhadap Revisit dengan Mediasi Kepuasan Konsumen Holland Bakery - Annisa Luthfiyah; Surya Bintarti; Muhamad Ali Maskuri (Journal on Education, 2023)
The current business in Indonesia, especially in the food sector, has grown rapidly over time. Based on environmental phenomena, bread is one of the favorite foods to replace rice. The millennial generation tends to want to try everything they see on the internet, for example, one of which is food. Various kinds of bakeries spread across Indonesia, sales of Holland Bakery always occupy the third position. Holland Bakery offers a variety of interesting products to consumers. This study aims to examine the relationship between perceived value and price on repurchase intentions through consumer mediation moderated by personal selling. This research uses quantitative methods. Sampling in this study used the Non Probability Sampling Method with a purposive technique. The population used by the community in Bekasi district. The samples obtained were 100 respondents, with data analysis in this study using regression. This study proves that: 1. The perceived value of Holland Bakery products can encourage consumers to repurchase Holland Bakery bakery products. 2. Prices set for Holland Bakery products can encourage consumers to repurchase. 3. The value felt by consumers for Holland Bakery products creates a feeling of satisfaction, so that it can encourage repurchasing. 4. The price set by the producer for Holland Bakery products creates a feeling of satisfaction, so that it can encourage repurchasing. 5. A high level of consumer satisfaction can encourage consumers to repurchase Holland Bakery products. 6. Personal selling has a direct role on customer repurchase intentions Holland Bakery. 7. Personal selling can play a role in strengthening the price of Holland Bakery consumer repurchase intentions.